Study of maternal and fetal outcomes in abruptio placenta at a tertiary care institute - Bhutada, Radhika G.; Kapote, Deepali S.; Chavan, Nirajan N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: This study aimed to determine the maternal and fetal outcomes in cases of abruptio placentae at a tertiary care institute. Methods: This prospective observational study was conducted from November 2022 to June 2024 at Lokmanya Tilak Municipal Medical College and Hospital, Sion, Mumbai. Out of 14,780 deliveries that occurred in this period, 143 were selected. The study included patients diagnosed with placental abruption, either clinically or radiologically, who presented to the ANC ward and consented to participate. Results: The study found a 0.9% incidence of placental abruption, predominantly seen in multigravida (68.5%) and women aged 21-30 years (70%). More than two-thirds of babies were born prematurely. The most common symptoms were vaginal bleeding and abdominal pain (75.5%), and hypertensive disorders of pregnancy were the most common associated factor (55.9%). Around 91.6% required lower segment cesarean section. 58.7% required blood transfusion. Complications included shock (4.2%), DIC (14.7%), acute renal failure (4.9%), sepsis (2.1%), cesarean hysterectomy (0.7%), and maternal mortality (0.7%). Additionally, 28% of women required ICU admission. The study found that 74.8% of deliveries resulted in live births, while 25.2% were stillbirths. Among the live births, 67 babies required NICU admission, and 7 (6.54% of live births) resulted in neonatal mortality. Conclusions: Abruptio placenta is a life-threatening complication of pregnancy and is associated with poor maternal and fetal outcomes if not managed appropriately. Hence, early diagnosis and prompt resuscitative measures would prevent both perinatal and maternal mortality and morbidity.